2019
DOI: 10.1149/2.1321912jes
|View full text |Cite
|
Sign up to set email alerts
|

3D Nitrogen and Sulfur Co-Doped Graphene/Integrated Polysaccharides for Electrochemical Recognition Tryptophan Enantiomers

Abstract: Polysaccharides based on carboxymethyl β-cyclodextrin (β-CD-COOH) and chitosan (CS) were synthesized by amidation reaction between -COOH on β-CD-COOH and -NH 2 on CS to develop the electrochemical sensors. The sensor was constructed by combining the advantages of the polysaccharide CS-β-CD and the guest molecule and the 3D N, S co-doped graphene (NSG). CS-β-CD was used as chiral selector can provide a large number of chiral sites and NSG served as base material can improve electrochemical signal. The enantiose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…28 The N 1s spectra can be deconvoluted into two peaks at 399.7 and 402.0 eV (Fig. 5C), which are related to CN 29 originating from the metal precursor ([(CH 3 CN) 4 Cu]PF 6 ) and C–N 30 originating from Taniaphos, respectively. The P 2p spectra can be divided into three peaks at 130.9, 132.4 and 136.1 eV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…28 The N 1s spectra can be deconvoluted into two peaks at 399.7 and 402.0 eV (Fig. 5C), which are related to CN 29 originating from the metal precursor ([(CH 3 CN) 4 Cu]PF 6 ) and C–N 30 originating from Taniaphos, respectively. The P 2p spectra can be divided into three peaks at 130.9, 132.4 and 136.1 eV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, there are no peaks for cMel-5, indicative of the non-existence of S in accordance with the EDS results. However, for cMel, there are two distinct peaks at BEs of 169.1 and 168.0 eV, corresponding to S 2p 1/2 and 2p 3/2 of SO, 41 respectively, and the peak position of cMel is ∼0.1 eV higher than that of Mel (Figure S5a). Figure 3d shows the O 1s corelevel spectra of samples.…”
Section: Resultsmentioning
confidence: 99%
“…The quantity of dissociative polar functional groups at the electrode interface was reduced, resulting in weakened wettability. In addition, the WCAs of BPNSs/GCE (Figure S6B), NH 2 -βCD/GCE (Figure S6C), SGO/GCE (Figure S6D), SGO-NH 2 -βCD/GCE (Figure S6E), and SGO-NH 2 -βCD/BPNSs/GCE (Figure S6F) in l -Tyr were smaller than those in d -Tyr, which indicated that the sensor interfaces possessed higher affinity toward d -Tyr than l -Tyr. , Importantly, the WCA of SGO-NH 2 -βCD/BPNSs/GCE immersed in l -Tyr and d -Tyr solutions increased to 69.00 and 82.38°, respectively, which might be due to the more suitable intermolecular distance and the preferably formed hydrogen bonds between d -Tyr and SGO-NH 2 -βCD/BPNSs, and SGO-NH 2 -βCD/BPNSs/GCE immersed in d -Tyr would show a relatively higher WCA . Furthermore, the differences in WCA of SGO-NH 2 -βCD/BPNSs/GCE impregnated in l -Tyr and d -Tyr were the largest, indicating that SGO-NH 2 -βCD/BPNSs/GCE possessed the highest ability to recognize Tyr enantiomers, which was consistent with the SWV results.…”
Section: Resultsmentioning
confidence: 99%
“…However, the conductivity of β-CD is relatively lower, while the combination of β-CD with conductive nanomaterials could greatly improve its electrochemical performance . Meanwhile, the dispersibility of composite materials were also found to be greatly improved and could be rationally regulated .…”
Section: Introductionmentioning
confidence: 99%